2015
DOI: 10.1002/chem.201502714
|View full text |Cite
|
Sign up to set email alerts
|

Towards Organized Hybrid Nanomaterials at the Air/Water Interface Based on Liquid‐Crystal/ZnO Nanocrystals

Abstract: The ability to self-assemble nanosized ligand-stabilized metal oxide or semiconductor materials offers an intriguing route to engineer nanomaterials with new tailored properties from the disparate components. We describe a novel one-pot two-step organometallic approach to prepare ZnO nanocrystals (NCs) coated with deprotonated 4-(dodecyloxy)benzoic acid (i.e., an X-type liquid-crystalline ligand) as a model LC system (termed ZnO-LC1 NCs). Langmuir and Langmuir-Blodgett films of the resulting hybrids are invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…Recently, our group developed a novel self-supporting organometallic approach for the synthesis of liquid crystalline carboxylate ligand-coated ZnO NCs which were effectively used for the preparation of highly-ordered hybrid nanomaterials at the air/water interface. 8 Simultaneously, we also demonstrated that ZnO NCs obtained by this organometallic procedure exhibit essentially a very low negative impact on mammalian cell lines. 9 We anticipated that the observed low cytotoxicity stems from the NC effective surface passivation and the impermeable organic shell.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Recently, our group developed a novel self-supporting organometallic approach for the synthesis of liquid crystalline carboxylate ligand-coated ZnO NCs which were effectively used for the preparation of highly-ordered hybrid nanomaterials at the air/water interface. 8 Simultaneously, we also demonstrated that ZnO NCs obtained by this organometallic procedure exhibit essentially a very low negative impact on mammalian cell lines. 9 We anticipated that the observed low cytotoxicity stems from the NC effective surface passivation and the impermeable organic shell.…”
mentioning
confidence: 53%
“…In order to verify our hypothesis that the self-supporting organometallic procedure provides ZnO NCs with the ligand shell sufficiently shielding against Cu ions during the CuACC process, we selected ZnO NCs stabilized by deprotonated 10-undecynoic acid (una-H) for Cu(I)-mediated click chemistry. Initially, the una ligandpassivated ZnO NCs (hereafter denoted as una-ZnO NCs) were synthesized according to the self-supporting method, 8 which involves: (i) the equimolar reaction between Et 2 Zn and una-H in a donor solvent and (ii) the exposure of the in situ synthesized [EtZn(una)] precursor 10 to air resulting in its subsequent transformation to una-ZnO NCs, forming stable colloidal solutions in THF, CHCl 3 and DMSO (Scheme 1). Prior to further processing and after the purification (see the ESI †), the una-ZnO NCs were characterized using a wide library of analytical techniques.…”
mentioning
confidence: 99%
“…96, 173, 174, 176-179, 208, 209 Lewiński and co-workers employed a simple 'one-pot, two-step' strategy of exposing a THF solution of ligated precursor [ZnEtL]n (L = [RCO2] − , [R2PO2] − or aminoalcoholate) to air, producing small (~2-8 nm) ZnO@L NPs with a dense surface coverage of ligand. 176,178,179 This synthetic route yields ZnO NPs described as (ZnO)x(ZnL2)y(L)z (L = monoanionic ligand) with more than a single monolayer of ligands. This ligand shell is described as 'impermeable', and protects the ZnO core, which results in slow photoluminescence (electron-hole separation up to 2.2 μs) 180 , giving these NPs enhanced properties relative to ZnO from sol-gel techniques.…”
Section: Ic Synthesis Of Zno Nps With Strongly Bound Anionic Ligandsmentioning
confidence: 99%
“…179 The process tolerates many different R groups upon the anionic ligand (Fig 24), for instance, the use of liquid crystalline carboxylates such as O2CC6H4OC12H25 allowed the preparation of ZnO NPs which self-assemble into free-standing thin films when compressed upon an air-water interface by the Langmuir method. 176,182 The films form via ligand interdigitation and retain the photoactivity of the individual ZnO NPs. Further studies showed that a Cu catalysed alkyne-azide cycloaddition reaction may be subsequently initiated on ZnO with alkyne terminated carboxylate ligands, and, unlike other NP preparation routes, these NPs remain luminescent after exposure to the Cu(I) catalyst, due to the as the impermeable surface layer of ligands.…”
Section: Ic Synthesis Of Zno Nps With Strongly Bound Anionic Ligandsmentioning
confidence: 99%
See 1 more Smart Citation